PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN Studi kasus pada perusahaan perbankan yang terdaftar di Bursa Efek Indonesia Tahun 2012-2015 - Rasyid, Elly; Pakpahan, Novi Yanti Tonggina; Hutajulu, Fharel M. (Universitas Kristen Indonesia, 2017)
This research aims is to determine the effect of good corporate governance (GCG) as measured by the commissioners (meeting activity), the board of directors, independent board and audit committee on the financial performance of banks as measured by return on assets (ROA). Data are obtained from secondary data in the form of annual reports and company GCG Report for the period 2012-2015 contained in www.idx.co.id. Sampling using purposive sampling. The results of this study indicate simultaneous testing with a significance level of 0.030 <0.05 states that the board of commissioners (meeting activity), the board of directors, independent board and audit committee have a significant effect on the financial performance listed on the Stock Exchange. Partially board of directors and have significant influence with a significant level of thitung 2.027> 1.98 ttabel. Commissioners (meeting activity) does not affect the level of singnifikan of the t (1.176) <t table (1.98) on financial performance. Independent board does not affect the show singnifikan level of thitung (-0.567) <t table (1.98) on financial performance. The audit committee does not affect the show singnifikan level of the t (1.580) <t table (1.98) on financial performance. In improving the financial performance, the company should use four variables of good corporate governance (GCG) in order to synergize in implementing policies that have been defined.Keywords: Board of Commissioners (meeting activity), the board of director, independent board and audit committee